PENYALAHGUNAAN KOREOGRAFI TARI PADA APLIKASI TIKTOK SEBAGAI KEKAYAAN INTELEKTUAL YANG DIKOMERSIALISASIKAN TANPA IZIN - Vanessa Christina Siringoringo (Universitas Warmadewa, Denpasar, Bali, 2023)
Dance choreography is generally created to be performed in public, but as technology advances, dance choreography is also recorded in video form to be performed through the TikTok application. Dance choreography published on the TikTok application is content that is often misused for the commercial interests of others. The creator can make several efforts when this happens because of the copyright that arises there are exclusive rights in it. This study aims to find out the concept of declarative principles in the Copyright Act and to find out the solution to the problem of abuse of dance choreography which was commercialized without the creator's permission. This study uses normative legal research, which takes a statutory and conceptual approach. The results of this writing research state that copyright has arisen after the work has been published based on the declarative principle and copyright that has arisen automatically has exclusive rights which are divided into moral rights and economic rights.